Sustainability in Educational Research: Mapping the Field with a Bibliometric Analysis - Donmez, Ismail (Mdpi, 2024)
This research uncovers contemporary patterns by employing the bibliometric analysis approach to analyze sustainability research in the education domain. Consequently, we map the academic outputs and observe a tendency of increased publications, which proves the growing interest in global sustainability imperatives with the help of WoS data. Regarding the publications, the United Kingdom, Germany, and the United States were the most productive, stressing an international focus and interdisciplinarity. The analysis showed that there was a shift in the topic focus from environmental education to sustainable education as a result of integrating SDGs into every level of education. As such, the results highlight the role of education in sustainability and necessitate more research for better evaluation and implementation of educational efforts. This study not only presents a history of the field but also sets a future agenda for the discipline, which is the significance of education for sustainability. In this way, our work enhances the knowledge of sustainability in education, and the results of our work lay a theoretical and methodological basis for further research and activities in the field.
Keywords: sustainability; educational research; bibliometric analysis; sustainable development